Analisis Deskriptif Hubungan Antara Latar Belakang Orang Tua Dengan Pencapaian Akademik Anak Studi Di Desa Alassumur Kulon - Nining Winarsih; Udkhuli Jannati (Contemporary Education Review, 2025)
In Indonesia, attention is focused on the phenomenon of low academic achievement among children, which is often associated with the role of parents in education. The aim of this research is to identify the relationship between parental roles and children’s academic achievement in the village. The research method employed is qualitative, with random sampling of four parents whose children are attending school. Data collection was carried out through observation, interviews, and documentation to understand parental involvement and children’s academic performance. The collected data was then analyzed descriptively. The results of the analysis revealed a significant positive relationship between active parental involvement and children’s academic achievement. These findings underscore the importance of parental support in improving children’s learning outcomes in the village.